A study of Ultra-High-Energy Cosmic Ray propagation in one-dimensional simulations - Olivares Schneider, José Gabriel (2021)
Cosmic Rays have come to play an important role in understanding the universe, and astroparticle physics has undergone major developments in the last few decades. As such, several observatories have been set up with the purpose of detecting these particles, and simulation frameworks have been developed in order to further analyze their behavior by creating highly variable environments and parameters. This work covers the essential theory required to study propagation of Ultra- High-Energy Cosmic Rays restricted to linear one-dimensional propagation only; this includes the primary methods of energy loss during propagation, mainly through reactions with the photon background like photo-pion production and photo-disintegration, and additional cosmological effects. The study was done using the CRPropa 3.0 simulation framework. To determine the best possible maximum energy for the simulations, initial trials were done by testing the GZK cutoff for multiple energy values, followed by an analysis of heavier nuclei propagation. As a final complete test run, a model of the cosmic ray spectrum for energies above 1018 eV was made based on two data sets, one made from the average composition of the whole CR energy spectrum, and the other from The Pierre-Auger Observatory measurements for the high energy range. The results showed that initial source composition was the determining factor in the shape of the CR spectrum. These initial simulations done in this work will set the ground for future more complex simulations and studies.